A novel EPM2A mutation in a patient with Lafora disease presenting with early parkinsonism symptoms in childhood. (October 2017) - Yildiz, Edibe Pembegul; Yesil, Gozde; Ozkan, Melis Ulak; Bektas, Gonca; Caliskan, Mine; Ozmen, Meral
Highlights: Lafora disease is an autosomal recessive form of progressive myoclonic epilepsy. We present a child with molecularly diagnosed LD who developed parkinsonism in early childhood. Lafora disease patient with a novel mutation in EPM2A gene presenting with early onset parkinsonism and severe neurocognitive decline.